Modelling the Integration of People with Disabilities into the Labor Market - Ravoaja, Hajaina (The Indonesian Institute of Science and Technology Research, 2025)
In this paper, a systematic review of the literature on the labor market integration (LMI) of people with disabilities (PWD) was conducted. PWD’s LMI is characterized by obtaining a (first) job, by the suitability of this job, by its security and maintenance, by a long-term career, by participation in the labor market, and by finding the meaning of this job. The stakeholder perspective of integrating PWD into the labor market could be extended to the long term. Thanks to the results and analysis supplied by this research, these partners will be able to channel their actions along the six phases identified. This article will enable the people involved to gain a better understanding of the phenomenon, solve the problems, and better assume their responsibilities. This study responds to the lack of literature review on the PWD’s LMI and provides an analysis and organization of this knowledge.